Regulatory authority and clinical acceptability: Physicians' responses to regulatory drug safety warnings. Issue 2 (16th August 2021) - Bhasale, Alice L.; Sarpatwari, Ameet; Lipworth, Wendy; Møllebæk, Mathias; McEwin, Eliza J.; Gautam, Nileesa; Santiago Ortiz, Adrian; Mintzes, Barbara J.
Abstract : Aims: Medicines regulators issue post‐market safety warnings to advise of newly uncovered risks, but with mixed impacts. We aimed to identify factors influencing the use of regulatory warnings by primary care and specialist physicians in the US and Australia. Methods: Semi‐structured qualitative interviews were carried out with 40 primary care physicians, endocrinologists and other generalist specialists in Boston (USA) and Australia. Coding and analysis were performed inductively and iteratively to identify and examine key factors. Analysis centred around four areas: physicians' awareness of drug safety information, preferred information sources, opinion‐forming and sharing of information with patients. Results: Uncertainty, trust and clinical authority emerged as factors influencing use of advisories. Although regulators were trusted as authoritative institutions, they appeared to lack clinical authority, and physicians validated regulatory information against other trusted sources including evidence, expert opinion and experience. Specialists became aware of drug safety issues through specialised literature, using evidence and clinical consensus to form opinions. Primary care physicians, fielding high volumes of information, relied on convenient, accessible information sources including the media and the "clinical grapevine" for awareness, and on clinical colleagues, specialists and experience for interpretation. Communicating risk to patients was complicated by uncertainty; physicians tailored information to patients' health literacy and information needs. US physicians were more aware of their national regulator's post‐market safety role than Australian physicians of theirs. Conclusion: Drug safety warnings may not be optimally received or used. Regulators should consider strategies that increase trust, clinical relevance and accessibility, and address physicians' needs in communicating risk to patients.